ANALISIS RETURN ON INVESTMENT (ROI) UNTUK MENILAI KINERJA KEUANGAN PADA PT. MITRA INVESTINDO, Tbk. - Hardiansyah, Dedy; Nurhayati, Nurhayati (J-ISCAN: Journal of Islamic Accounting Research., 2021)
The purpose of this study is to find out how much Return On Investment (ROI) is to assess the financial performance of PT Mitra Investindo, Tbk. This type of quantitative descriptive research uses secondary data. Data collection techniques are documentation and literature study. Research population for 22 years from the start of listing on the Indonesia Stock Exchange 1997-2019. Then a sample of 10 years from 2010-2019 with purposive sampling technique. The data analysis technique used statistical analysis with a one-sample t-test. The results showed that the Return On Investment (ROI) to assess the financial performance of PT Mitra Investindo, Tbk was in a bad condition because it was less than 30% of the expected.